2014
DOI: 10.1080/17461391.2014.933879
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration and sprint profiles of a professional elite football team in match play

Abstract: The aim of this study was to characterise the acceleration and sprint profiles of elite football match play in one Norwegian elite football team (Rosenborg FC). Fifteen professional players in five playing positions took part in the study (n = 101 observations). Player movement was recorded during every domestic home game of one full season (n = 15) by an automatic tracking system based on microwave technology. Each player performed 91 ± 21 accelerations per match, with a lower number in the second compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
5
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(161 citation statements)
references
References 36 publications
9
118
5
6
Order By: Relevance
“…Whereas our study showed the total number of accelerations and decelerations above 1.5 m · s −2 (226 and 169, respectively) and 3.0 m · s −2 (61 and 58), other studies that considered matches in elite leagues (Bradley et al 2010;Varley & Aughey 2013;Russell et al 2014;Wehbe et al 2014;Ingebrigtsen et al 2015;Dalen et al 2016) used absolute thresholds of 0.5, 2.0, 2.5, 2.78, 3.0 and 4.0 m · s −2 . It is important to realize that even if there was agreement, comparison between acceleration variables measured with different tracking systems (and system versions) would be difficult (Buchheit et al 2014b).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Whereas our study showed the total number of accelerations and decelerations above 1.5 m · s −2 (226 and 169, respectively) and 3.0 m · s −2 (61 and 58), other studies that considered matches in elite leagues (Bradley et al 2010;Varley & Aughey 2013;Russell et al 2014;Wehbe et al 2014;Ingebrigtsen et al 2015;Dalen et al 2016) used absolute thresholds of 0.5, 2.0, 2.5, 2.78, 3.0 and 4.0 m · s −2 . It is important to realize that even if there was agreement, comparison between acceleration variables measured with different tracking systems (and system versions) would be difficult (Buchheit et al 2014b).…”
Section: Discussionmentioning
confidence: 63%
“…The average total distance ran during the matches in our study (10,927 m) reflected that of top-level leagues in Europe and Australia (range 10,063-11,230 m) (Bradley et al 2010(Bradley et al , 2013Osgnach et al 2010;Manzi et al 2014;Wehbe et al 2014;Ingebrigtsen et al 2015;Dalen et al 2016). Also running (14.4-19.8 km · h −1 ) distance and high-speed running (>19.8 km · h −1 ) distance were within the range of the same top-level leagues (1614 m vs. 1612-1758 m and 738 m vs. 646-1061 m, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Match running performance in elite Gaelic football 10 the rules of each specific game, all of which will influence findings in addition, to the variation in speed thresholds across studies for high speed distance (23,25) . Sprint actions have been reported to have a positive effect on match outcomes within soccer (23, 25 41) .…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Reductions in acceleration capacity are found between halves and transiently during the game. Between playing halves, a decline is reported in the number of efforts (Ingebrigtsen, Terje, Hjelde, Drust, Wisloff, 2015;Russell et al, 2014;Terje, Ingebrigtsen, Gertjan, Harvard, Wisloff, 2015) and the cumulative distance (Terje et al, 2015;Akenhead, Hayes, David J. Barron, Steve Atkins, Chris Edmundson, Dave Fewtrell Thompson, Duncan, 2013;Barron, Atkins, Edmundson, Fewtrell, 2014).…”
Section: Introductionmentioning
confidence: 99%